Pengaruh Budaya Organisasi dan Kedisiplinan Kerja Terhadap Kinerja Karyawan Bagian Produksi Pt YKK Zipco Indonesia - Rizka Arifiani; Inna Nisawati Mardiani (Public Service and Governance Journal, 2023)
Management of qualified, adaptive, and innovative human resources plays an important role in the digital transformation era. According to the Minister of Manpower Ida Fauziyah, this will support national economic recovery. In addition, building HR resilience for company safety and health is an important function of HRM. Employee health is also a crucial factor in maintaining business continuity. Based on news quotes from CNN Indonesia, HRM has a vital role in creating quality human resources to achieve optimal employee performance. Organizational culture and work discipline are driving forces to improve the quality of employee work. Organizational culture has long been used in daily activities to improve work quality. Meanwhile, discipline is an attitude of respect and following the rules. R2 test results show numbers Adjusted R Square of 0.741 or 74.1% which means the Organizational Culture variable (X1) and Work Discipline (X2) both affect performance (Y) by 74.1% while the remaining 25.9% are influenced by other variables. Organizational Culture (X1) partially affects employee performance (Y) with a t count of 3.369 > t table of 1.98447. Work Discipline (X2) partially affects Employee Performance (Y) with a t count of 6390 > t table of 1.98447. X1 and X2 variable simultaneously have a positive effect on variable Y with a calculated f value of 138.779 > f table 3.09.